Management Of Education Quality Achievements Based On Quality Report Card Results At UPT SMP Negeri 2 Bangkala School, Jeneponto Regency - Nurul Fatimah; Wahira (Cita konsultindo, 2025)
Management of Educational Quality Achievement Based on the Results of the Quality Report Card at the State Junior High School 2 Bangkala Regency. Thesis. Educational Administration Study Program, Specialization of Educational Management, Postgraduate Program, State University of Makassar. (Guided Wahira) . This study examines the management of educational quality achievement based on the results of the quality report card at UPT SMP Negeri 2 Bangkala school, Jeneponto Regency. The purpose of this study is to analyze how the planning, implementation and evaluation stages of the management of educational quality achievements based on the results of the quality report card as well as the supporting factors and inhibiting factors of the management of educational quality achievement based on the results of the quality report card at the UPT SMP Negeri 2 Bangkala school, Jeneponto Regency. Types of qualitative research with a descriptive approach. The data from the research was obtained using interview, observation, and documentation techniques, namely data reduction, data presentation, and conclusion drawn. The results of the study show that the planning to improve the quality of education at UPT SMP Negeri 2 Bangkala is carried out based on the results of the school quality report card with a strategy that includes strengthening the curriculum and improving teacher competence. Program implementation involves various parties and emphasizes interactive approaches as well as extracurricular programs. Evaluation is used to assess the effectiveness of the program, although the monitoring system still needs to be strengthened. Supporting factors include laboratories, conducive learning environments, and teachers who are active in training, while barriers such as distance, limited facilities, and lack of innovation and communication need to be addressed with more effective strategies.